IMPLEMENTASI PENGENDALIAN SEDIAAN CAT DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) DI UD. BUMI INDAH JAYA ABADI SURABAYA - Andy Gozali (Perpustakaan Universitas Surabaya, 2016)
This Study to Implementation of inventory controlling is to optimate the Vircan Paint quantity so if fluctuation demand happens it can fulfill that consumer demand. Also to define the appropriate forecasting method for Vircan Paint product at UD Bumi Indah Jaya Abadi This Implementation of inventory controlling used the EOQ method, also the calculation of Safety Stock, Reorder Point, ordering frequency, Ordering interval, and Maximum inventoy. The usage of this EOQ method is to define the appropriate inventory quantity when it had the stock ordering to minimize the company cost. To define the level of inventory quantity, the usage variabel is the relevant cost, like : purchasing cost, ordering cost, and holding coAfter the calculation with EOQ method done with the different level of service level,next we will do the comparation analysis of calculation cost that use EOQ method with the different Service Level Value and with the company policy. The result is the difference saving with EOQ method with the 100% service level as much as 12,39%.